Analytical methods, formation, and dissolution of cinnabar and its impact on environmental cycle of mercury. Issue 24 (17th December 2017) - Chen, Ying; Yin, Yongguang; Shi, Jianbo; Liu, Guangliang; Hu, Ligang; Liu, Jingfu; Cai, Yong; Jiang, Guibin
ABSTRACT: Mercury sulfide (HgS, cinnabar, and metacinnabar) is a major Hg sink, widely available in various environmental compartments. The formation and dissolution of HgS play a crucial role in the geochemical cycle of Hg, including its transport, reduction, methylation, and toxicity. Unlike other Hg species (e.g., methylmercury, Hg 0 ), environmental HgS occurs in the form of different sized particles, leading to various challenges regarding its quantification and the evaluation of potential environmental impacts. This review summarizes the current analytical methods for the identification, characterization, and quantification of HgS, including sequential chemical extraction, X-ray absorption spectroscopy, programmed thermal desorption, and selective vapor generation, among other methods. In addition, the chemical/biological pathways and mechanisms involved in the formation and dissolution of HgS are reviewed, as are the analytical and environmental perspectives of HgS. This review furthers our understanding and encourages the study of the environmental formation and dissolution of HgS and its role in the geochemical cycle of Hg.